(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
Recensiamo l’edizione italiana, curata da Massimo Bonafin, del libro di Eleazar Moiseevič Meletinskij Archetipi letterari. Trad. Laura Sestri. Macerata: eum, 2016. Review of the Italian edition of Eleazar Moiseevič Meletinskij’s book Archetipi letterari, edited by Massimo Bonafin. Translation by Laura Sestri. Macerata: eum, 2016.